Recent Advances in Chromium-Catalyzed Organic Transformations - Zeng, Xiaoming (Synlett, 2020)
The use of simple and low-cost chromium chloride salts as catalysts or precatalysts for the development of cost-effective methods is of significant synthetic and mechanistic interest. Here, recent advances in chromium-catalyzed organic transformations are highlighted.1 Introduction2 Arylmagnesiation of Alkynes3 Catalytic Functionalization of C(aryl)–O Bonds4 Catalytic Functionalization of C(aryl)–N Bonds5 Catalytic Functionalization of C(aryl)–H Bonds6 NHK-Type Reactions7 Hydrogenation8 Conclusions
Keywords: chromium; homogeneous catalysis; cross-coupling; hydrogenation